Analysis of the Financial Soundness of Footwear Industry in Bangladesh: An Empirical Study using Z-score - Jahan, Ishrat; Zaman, Fareen (Global Disclosure of Economics and Business, 2017)
Among all the available statistical techniques, Altman’s Z-score is found to be the most reliable technique to measure the financial soundness of any given business organization. In this paper, we have selected footwear industry which is the second largest foreign currency earner in Bangladesh. This industry is contributing in a greater scale to the economy of our country. The prime objective of this study is to assess the financial heath, i.e. analyze the probability of bankruptcy of the listed companies of the footwear industry. We have studied the financial statements of five companies listed in the stock exchange for a period of 2011 to 2015. The study revealed that the footwear industry overall is in a safe position i.e. financially sound, showing two of the selected companies in the safe zone, one in the grey zone and two in the distress zone. The findings of the study will help different groups of stakeholders to make decisions regarding their investments and other choices, considering the soundness of this specific industry.